A journey to measure student community engagement benefits: evidence from Australia / Ellen Chung and Hamish Coates - Chung, Ellen; Coates, Hamish (Universiti Teknologi MARA Cawangan Sarawak, 2016)
Community engagement is a phenomenon that has received increasing attention among institutions of higher learning in recent years, and students engaging with communities are generally seen as beneficial. Given this, surprisingly little is known about this form of engagement in Australian higher education, let alone methods to measure its benefits on students. This study discussed the development of the Student Community Engagement Benefits Questionnaire (SCEBS), a questionnaire that measures the perceptions of community engagement benefits among undergraduate students in Australia. The final questionnaire has 32 items allocated to four benefit scales: (1) Career skills, (2) Diversity skills, (3) Interpersonal skills, (4) Civic skills. Most benefit items had a factor loading of at least 0.40 with its own scale. The results of the factor analysis revealed that the four scales accounted for 53% of the total variance. The alpha reliability coefficient for the four scales ranged from 0.79 to 0.91. Based on these findings, the Student Community Engagement Benefits Scale (SCEBS) is a valid and reliable instrument that can be used in the field of education. Undergraduate students also reported statistically significant changes in the four dimensions after participating in community engagement activities.